Stres Psikis Tidak Berkaitan dengan Timbulnya Sindrom Premenstruasi - Cherryl Martha Christina Anggreani Winoto; Slamet Riyadi; Andri Iryawan (Nexus Kedokteran Komunitas, 2013)
Background:High school students have a potential risk of stress that caused by the demands of their school life. Stressors increased when they were in grade XII in which they would do national exam. Stress condition have a negative impact on their health, one of which will cause occurenceof premenstrual syndrome. The aim of this research was to investigate the relationship between psychological stress before doing national exam and premenstrual syndrome. Methods:The research design of this study was analytical descriptive with cross sectional approach. The subjects were female students in grade XII who took a special course for preparing National Exam at Surakarta. Data was collectedby used purposive random sampling technique. There were 60 female students to fill the questionnaires, 30 students as stress group and the other were control group. Collected data was annalizedwithFishers Exact formula. Results:In stress group, there were 28 students with premenstrual syndrome and 2 students without premenstrual syndrome. In control group, there were 26 students with premenstrual syndrome and 4 students without premenstrual syndrome. Result of the statistical test provided there was no relationship between stress and premenstrual syndrome (p = 0.671).Among the samples, there were 49 students with anxiety and the statistical test suggested there was relationship between anxiety and premenstrual syndrome (p = 0.008) Conclusions:This result provided there was no relationship between psychological stress before doing national exam and premenstrual syndrome for senior high school female students at special course in Surakarta. For further research, it is recommended to classified stress as mild, moderate, severe and extremely severe. Keywords:psychological stress; national exam; premenstrual syndrome.